Market Phase and the Stationarity of Beta - Gooding, Arthur E.; O'Malley, Terence P. (Journal of Financial and Quantitative Analysis, 1977)
This paper examines the stationarity of beta coefficients, especially in regard to recent, major stock market trends. In addition to the usual correlation tests for stationarity, this paper describes a more direct method for testing the stationarity of portfolio betas. The method involves the use of paired t-tests which show separately the degree of stationarity for each portfolio beta. In the process of testing for stationarity, the portfolio betas also are adjusted for measurement error using a formulation suggested by Blume [3].